Cytophilic Antibodies Against Key Plasmodium falciparum Blood Stage Antigens Contribute to Protection Against Clinical Malaria in a High Transmission Region of Eastern India. (4th May 2018) - Kana, Ikhlaq Hussain; Garcia-Senosiain, Asier; Singh, Susheel K; Tiendrebeogo, Régis Wendpayangde; Chourasia, Bishwanath Kumar; Malhotra, Pawan; Sharma, Surya K; Das, Manoj K; Singh, Subhash; Adu, Bright; Theisen, Michael
Abstract : Opsonic phagocytosis of Plasmodium falciparum merozoites was associated with protection against clinical malaria in an India population. Antibody profiling identified four merozoite antigens (Pf12, MSP3.7, MSP3.3, and MSP2) as targets of protective Immunoglobuline G3 antibodies. Abstract: Background: The collection of clinical data from a tribal population in a malaria-endemic area of India suggests the occurrence of naturally acquired immunity (NAI) against Plasmodium falciparum malaria. Methods: Quantity and functionality of immunoglobulin G (IgG) antibodies against intact merozoites and recombinant proteins were assessed in a 13-month longitudinal cohort study of 121 individuals, 3–60 years of age. Results: Opsonic phagocytosis of merozoites activity was strongly associated (hazard ratio [HR] = 0.34; 95% confidence interval [CI] = .18–.66; P = .0013) with protection against febrile malaria. Of the different IgG subclasses, only IgG3 antibodies against intact whole merozoites was significantly associated with protection against febrile malaria (HR = 0.47; 95% CI = .26–.86; P = .01). Furthermore, a combination of IgG3 antibody responses against Pf 12, MSP3.7, MSP3.3, and MSP2 FC27 was strongly associated with protection against febrile malaria (HR = 0.15; 95% CI, .06–.37; P = .0001). Conclusions: These data suggest that NAI may, at least in part, be explained by opsonic phagocytosis of merozoites and IgG3 responses against whole merozoites, and in particular to a combination of 4 antigens is critical in this population. These results may have implications in the development of a subunit malaria vaccine. Opsonic phagocytosis of Plasmodium falciparum merozoites was associated with protection against clinical malaria in an India population. Antibody profiling identified four merozoite antigens (Pf12, MSP3.7, MSP3.3, and MSP2) as targets of protective Immunoglobuline G3 antibodies.